Ocean Transportation Basics - Sri Kartini; Novrianti Novrianti; Shanty Katharina (IWJ : Inland Waterways Journal, 2020)
The development of transportation is currently developing very rapidly, this is in line with the human need for transportation which is increasingly complex. Transportation is the transfer of goods or people from one place to another using a vehicle driven by a machine or human power. Transportation is useful for making it easier for humans to carry out their daily activities. With the development of technology in the field of transportation, humans are greatly facilitated by the many means of transportation such as ships that can travel long distances in a short time. Shipping goods by ship is very cheap when compared to other types of transportation. Ships have the ability to transport goods in very large quantities. The characteristics of goods sent by ship are the types of goods that can last a long time, in very large quantities. Also supported by the existence of facilities and infrastructure that are developing as it is now that makes it easier to transport, transfer goods or people from one place to another. There are facilities that support transportation that can be used. Such a port can be used as a berth for ships that will transport and move goods or people. The port is also a gateway to enter a certain area and as a connecting infrastructure between regions, between islands, and even between countries. Also supported by the existence of facilities and infrastructure that are developing as it is now which makes it easier to transport, transfer goods or people from one place to another.